Auricular acupuncture for substance use: a randomized controlled trial of effects on anxiety, sleep, drug use and use of addiction treatment services. Issue 1 (December 2016) - Ahlberg, Rickard; Skårberg, Kurt; Brus, Ole; Kjellin, Lars
Abstract Background A common alternative treatment for substance abuse is auricular acupuncture. The aim of the study was to evaluate the short and long-term effect of auricular acupuncture on anxiety, sleep, drug use and addiction treatment utilization in adults with substance abuse. Method Of the patients included, 280 adults with substance abuse and psychiatric comorbidity, 80 were randomly assigned to auricular acupuncture according to the NADA protocol, 80 to auricular acupuncture according to a local protocol (LP), and 120 to relaxation (controls). The primary outcomes anxiety (Beck Anxiety Inventory; BAI) and insomnia (Insomnia Severity Index; ISI) were measured at baseline and at follow-ups 5 weeks and 3 months after the baseline assessment. Secondary outcomes were drug use and addiction service utilization. Complete datasets regarding BAI/ISI were obtained from 37/34 subjects in the NADA group, 28/28 in the LP group and 36/35 controls. Data were analyzed using Chi-square, Analysis of Variance, Kruskal Wallis, Repeated Measures Analysis of Variance, Eta square (η2 ), and Wilcoxon Signed Ranks tests. Results Participants in NADA, LP and control group improved significantly on the ISI and BAI. There was no significant difference in change over time between the three groups in any of the primary (effect size: BAI, η2 = 0.03, ISI, η2 = 0.05) or secondary outcomes. Neither of the two acupuncture treatments resulted in differences in sleep, anxiety or drug use from the control group at 5 weeks or 3 months. Conclusion No evidence was found that acupuncture as delivered in this study is more effective than relaxation for problems with anxiety, sleep or substance use or in reducing the need for further addiction treatment in patients with substance use problems and comorbid psychiatric disorders. The substantial attrition at follow-up is a main limitation of the study. Trial registration Clinical TrialsNCT02604706 (retrospectively registered).